The Concept of Judge’s Forgiveness (Rechterlijk Pardon) in The National Criminal Law Code - Anwar, Arizal; Suhartono, Slamet; Arie Mangesti, Yovita; Herlin Setyorini, Erny (Doctor of Law Study Program Faculty of Law, Universitas 17 Agustus 1945 Surabaya, 2025)
The absence of provisions regulating Judicial Pardon (Rechterlijk Pardon) in the current Indonesian Penal Code and Criminal Procedure Code has created a legal vacuum. Judges are normatively bound to issue one of three verdicts: conviction, acquittal, or dismissal. This limitation excludes the possibility for judges to apply discretionary forgiveness in cases involving minor offenses or mitigating circumstances. Although Article 54 paragraph (2) of Law No. 1 of 2023 concerning the Penal Code introduces the concept of Rechterlijk Pardon, it fails to provide clear parameters regarding what constitutes “minor severity of the act,” as well as the personal background of the offender or contextual factors surrounding the offense. This vagueness raises concerns over legal uncertainty and inconsistency in judicial interpretation. The purpose of this study is to examine the normative foundation and interpretive scope of the Judicial Pardon doctrine under Article 54 paragraph (2) and to formulate a legal construction that harmonizes substantive and procedural criminal law. This research is normative in nature, using a combination of statutory, conceptual, philosophical, case, and comparative approaches. The findings demonstrate that Judicial Pardon must be explicitly regulated through clear interpretive guidelines to ensure its implementation does not conflict with the principles of justice and legal certainty. Moreover, the integration of Judicial Pardon into the Draft Criminal Procedure Code is necessary to provide formal procedural legitimacy for judges to refrain from sentencing in specific circumstances, thus ensuring the penal system accommodates fairness, humanity, and proportionality in the enforcement of criminal justice.